Pictograms as Visual Communication. Tools for the Autonomy and Accessibility of Persons with Intellectual Disabilities - Girish Muzumdar; Asha Deshpande; Ben Howell Davis (Ocula)
The social inclusion of persons with disabilities is a priority in a growing number of countries. Their level of autonomy, with or without technical aids, is an essential criterion of its success. Pictograms are the technical aids of choice for persons with intellectual disabilities. The coherence of the pictographic tool is essential to the user-friendliness of such aids. Pictogram-based solutions are not only useful for persons with intellectual disabilities. They can be used by all those who have difficulties reading, such as illiterate persons, tourists, senior citizens, children, refugees, asylum-seekers, etc. Taken together, they can represent up to 30% of the population.